(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
In recent years, authorities in Bosnia and Herzegovina with support of international organizations achieved very important goals in improving respect for children’s rights in area of juduciary, police and social protection. Also, similar process is happening in countries in region, which is very important indicator of unification of policy makers to make their society better place for all citizens and vulnerable categories such as juvenile offenders, victims and witnesses. Bosnia and Herzegovina has complex state organization- two entities and one District, which means three different legislatives. Not only in justice for children system but also in all attempts on improving any other system, decision makers must be aware that they need to deal with three processes at same time. As every social change, these changes take time, motivation and resources. Policy makers in Bosnia and Herzegovina did recognize urgent need to make this area more structured and through working plans agreed with three Governments in Bosnia and Herzegovina, there is tendency that in the following period, system of juvenile justice will be improved, based on experiences from past and on vision and desire to make society of Bosnia and Herzegovina as society safe and healthy for all families. Using comparative analysis, description and methods of abstraction and concretization, this Paper will show justice system in Bosnia and Herzegovina with focus on justice for children, in reflection with area of human rights contained in European Law. System of child protection is extremely complexed and sensitive, and in process of creating surrounding best for them, Bosnia and Herzegovina’s society must show the will, motivation and great energy in strengthening justice for children.